SERTULUM DIPTEROCARPACEARUM MALAYENSIUM-”V* - D. F. VAN SLOOTEN (BRIN Publishing (Penerbit BRIN), 1952)
Some 70 years ago Thiselton Dyer showed Dipterocarpaceae from New Guinea to the Linnean Society of London. This event is referred to in the